PENGARUH PENDIDIKAN DAN PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. TELKOM KOTA PAREPARE - Winda, Winda; Parman, Parman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
Thesis of Management Study Program, Faculty of Economics and Business. Muhammadiyah University of Parepare. The purpose of this study was to determine and analyze the effect of education and employee placement on the performance of PT Telkom Parepare employees. The object of this research is the employees of PT Telkom Parepare. To obtain data to support this research, the researcher used a questionnaire method with a sample size of 50 employees. The data analysis tool used in this research is a study with multiple linear regression models. Based on the results of the research that has been done, it shows that: 1) Education has no significant effect on the performance of PT Telkom Parepare employees. 2) Employee placement affects the performance of PT Telkom Parepare employees.